2022
DOI: 10.1080/15592294.2022.2145068
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty4 is epigenetically upregulated in human colorectal cancer

Abstract: Sprouty4 (SPRY4) has been frequently reported as a tumor suppressor and is therefore downregulated in various cancers. For the first time, we report that SPRY4 is epigenetically upregulated in colorectal cancer (CRC). In this study, we explored DNA methylation and hydroxymethylation levels of SPRY4 in CRC cells and patient samples and correlated these findings with mRNA and protein expression levels. Three loci within the promoter region of SPRY4 were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…④Excessive methylation: Excessive methylation of the SPRY4 gene promoter region can lead to gene silencing and downregulation of expression, resulting in the loss of its regulatory role in cellular signaling transduction. High methylation in the SPRY4 promoter region has been observed in patients with prostate cancer ( 67 ), colorectal cancer ( 68 ), and familial testicular cancer ( 69 ), leading to transcriptional inactivation of SPRY4 and promoting tumor occurrence and development. In human colorectal cancer tumors, overexpression of UHRF1 upregulates SPRY4 transcriptional activity by regulating 5-hydroxymethylcytosine levels in the SPRY4 locus, promoting tumor development ( 70 ).…”
Section: The Role Of Spry4 In Malignant Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…④Excessive methylation: Excessive methylation of the SPRY4 gene promoter region can lead to gene silencing and downregulation of expression, resulting in the loss of its regulatory role in cellular signaling transduction. High methylation in the SPRY4 promoter region has been observed in patients with prostate cancer ( 67 ), colorectal cancer ( 68 ), and familial testicular cancer ( 69 ), leading to transcriptional inactivation of SPRY4 and promoting tumor occurrence and development. In human colorectal cancer tumors, overexpression of UHRF1 upregulates SPRY4 transcriptional activity by regulating 5-hydroxymethylcytosine levels in the SPRY4 locus, promoting tumor development ( 70 ).…”
Section: The Role Of Spry4 In Malignant Tumorsmentioning
confidence: 99%
“…In 2023, Alexei J. Stuckel et al analyzed the sequencing data of SPRY4 in gastric cancer tissues from the GEO database and TCGA database and found that the transcript levels of SPRY4 were increased in colorectal cancer patients compared to adjacent colonic and healthy mucosal control groups. This may be related to hypomethylation in the distal promoter region of CRC patients (68). DNA methylation is closely related to cancer development (71), and DNA methylation changes include hypermethylation and hypomethylation.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Thus, DNA methylation is a reversible and dynamic process [72]; its impairment leads to a global or gene-specific hypomethylation or hypermethylation and the loss of imprinting, alterations that are frequently detected in cancer onset and progression [73][74][75][76][77][78].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Epigenetic modifications, specifically 5-hydroxymethylcystones (5hmC) have emerged as novel cancer biomarkers, given their relevance in regulating both tissue-specific gene expression 12 and aberrant expression in cancers. 13 Previous studies suggested that global 5hmC is differentially modified in various solid tumors, including CRC, 1416 indicating their potential for detection and as diagnostic biomarkers for CRC. Of particular interest is the development of a minimally-invasive blood-based test for CRC occurrence that targets differential epigenetic modifications associated with CRC development.…”
Section: Introductionmentioning
confidence: 99%